2019
DOI: 10.1016/j.fuel.2019.115766
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of pilot-fuel combustion in dual-fuel engines, Part 2: Understanding the underlying mechanisms by means of optical diagnostics

Abstract: The pilot-fuel auto-ignition and combustion under engine like conditions in compressed methane/air mixtures have been investigated. Experiments were performed in an optically accessible Rapid Compression-Expansion Machine featuring quiescent charge conditions and a single-hole coaxial diesel injector mounted on the cylinder periphery. In Part 1, the phenomenology of the pilot-fuel combustion has been studied based on the thermodynamic analysis. With the addition of methane, a strongly prolonged pilot-fuel comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
4
9
0
Order By: Relevance
“…3, the light sheet was slightly tilted to match the 5° injector inclination. Since the fuel spray is pushed towards the piston head during the compression stroke, Srna et al [31] found that the effective symmetry axis of the spray cone has an angle of 3.5°, which was adopted for the arrangement of the light sheet in the present experiments. In both setups, LIF signals were directed towards a LaVision HSS6 high speed camera equipped with a high speed image intensifier (HS-IRO, gate width 150 ns, gain 62) using the same dichroic mirror (4'', HR 45 300-450 nm).…”
Section: Operating Strategy and Heat Release Rate Analysismentioning
confidence: 99%
“…3, the light sheet was slightly tilted to match the 5° injector inclination. Since the fuel spray is pushed towards the piston head during the compression stroke, Srna et al [31] found that the effective symmetry axis of the spray cone has an angle of 3.5°, which was adopted for the arrangement of the light sheet in the present experiments. In both setups, LIF signals were directed towards a LaVision HSS6 high speed camera equipped with a high speed image intensifier (HS-IRO, gate width 150 ns, gain 62) using the same dichroic mirror (4'', HR 45 300-450 nm).…”
Section: Operating Strategy and Heat Release Rate Analysismentioning
confidence: 99%
“…The phenomenology of DF combustion and its underlying processes have been described to some degree in previous optical studies. 12,13 In these studies, an optically accessible rapid-compression-expansion machine (RCEM) equipped with a single-hole coaxial diesel injector is utilized to investigate the DF combustion, as it transitions from ignition to premixed-flame combustion using thermodynamic analysis as well as OH* chemiluminescence imaging and planar laser-induced fluorescence (PLIF) imaging of CH 2 O. The optical diagnostics showed that CH 4 increases the ignition delay and prolongs the pilot-fuel combustion duration.…”
Section: Introductionmentioning
confidence: 99%
“…In dual-fuel mode, due to the pilot injection of reactive fuel (as diesel fuel), there is the added complexity of the poorly understood physicochemical interactions of the gaseous syngas combustion interactions with the liquid pilot fuel spray. Currently, natural gas or methane dual-fuel operation are well covered by the literature [17][18][19][20][21] but syngas less. Moreover, to correctly optimize dual-fuel syngas CI engines, the effects of its composition should be well understood.…”
Section: Hrr Heatmentioning
confidence: 99%